The effect of technology social media and knowledge shared between generations X’ers, generation Y towards the effective communication at University Teknologi Mara Campus Jengka Pahang / Wan Roshilawati Wan Sahidin - Wan Sahidin, Wan Roshilawati (Faculty of Business and Management, 2017)
The effective communication is the important in the conversation between two people to deliver the information in the right ways. Every generation have their own ways to communication among them. In this research to investigate between the two generation which is Gen X ers and Gen Y and to see how far the generation used technology, social media and knowledge toward the effective communication. This study was carried on the Universiti Teknologi Mara Kampus,Pahang is the one of the education institution which responsible in providing a good education to youth to get the knowledge. Other than that, the study focused on the staff in the Universiti Teknologi Mara Jengka that how they communicate among them. The effective communication has been measure through the element of communication which is technology, social media and knowledge shared. The sampling technique used in this research is convenience sampling